Building type basics for elementary and secondary schools - Perkins, L. Bradford; Bordwell, Raymond (Hoboken, N.J. : John Wiley & Sons, 2010)
Written by an experienced architect, Building Type Basics for Elementary and Secondary Schools explains key elements of school design through descriptive diagrams and photos. This comprehensive guide provides the foundation of architectural design of elementary and secondary schools.
Preface (John Czarnecki). Acknowledgments --
1. Predesign --
Introduction --
The Learning Process --
School Programming and Planning Guidelines --
Early Childhood and Kindergarten --
Elementary Schools --
Middle Schools and High Schools --
Special Schools --
Future School Facility Spaces --
2. Circulation --
Design Concepts --
Building Configurations --
3. Design Concerns and Process --
The Planning, Design, and Implementation Process --
Common Problems and Cautions --
Trends in School Planning and Design --
Unique Design Concerns --
4. Site Planning --
Urban Site Selection --
Suburban Site Selection --
Site Size --
Site Circulation --
Site Programming --
Elementary School Play Areas --
Security and Safety Concepts in Site and Building Design --
Sustainable Site Design --
5. Codes --
Life Safety --
Space Standards --
Appropriate Building Systems and Construction Practices --
Public Policy --
Fiscal and Anticorruption Controls --
Land-Use Policy --
Conclusion --
6. Sustainable Design Issues --
Sustainable Sites --
Water Efficiency --
Energy Conservation --
Building Envelope --
Materials and Resources --
Caveats --
7. Structural Systems --
Building Life --
Fire Safety --
Seismic Considerations --
Flexibility --
Cost --
Aesthetics --
Long-Span Spaces --
Prefabricated and Preengineered Structures --
Foundations --
Special Issues --
8. Mechanical Systems --
General --
Preschools and Kindergartens --
Elementary Schools --
Middle and Secondary Schools --
9. Electrical/Communications Systems --
Reference Standards --
Impact of Technology --
Power Source --
Emergency Power --
Lighting Systems --
Fire Safety --
Communications --
Space Requirements: Rules of Thumb --
10. Technology and Special Equipment --
Technology's Impact on Learning Space Design --
11. Materials --
Introduction --
Common Material Selections for Primary Spaces --
Durability and Maintenance --
Codes --
Regional Issues --
Environmental Considerations --
Considerations in Material Selection for Schools --
12. Acoustic Control --
Introduction --
Definitions --
Acoustical Performance: Materials an.
First ed. published as: Elementary and secondary schools / Bradford Perkins. c2001.
Includes bibliographical references and index.
ARC
Karim International
Keywords: Elementary school buildings -- United States -- Design and construction; High school buildings -- United States -- Design and construction; Elementary school buildings -- United States -- Planning; High school buildings -- United States -- Planning; Architecture